2023
DOI: 10.1021/acs.jpclett.3c00828
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron Spectroscopy of Oppositely Charged Molecular Switches in the Aqueous Phase: Theory and Experiment

Abstract: XUV photoelectron spectroscopy (XPS) is a powerful method for investigating the electronic structures of molecules. However, the correct interpretation of results in the condensed phase requires theoretical models that account for solvation. Here we present experimental aqueous-phase XPS of two organic biomimetic molecular switches, NAIP and p-HDIOP. These switches are structurally similar, but have opposite charges and thus present a stringent benchmark for solvation models which need to reproduce the observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 95 publications
0
1
0
Order By: Relevance
“…We found that for lumiflavin in solution, using a few quantum mechanically treated water molecules nearby as well as a hybrid ONIOM/PCM approach to treat long-range electrostatic effects of the solvent is necessary to simulate the experimental FTIR spectrum. We note also the importance of long-range interactions for simulating other properties in the condensed phase, such as UV–visible spectra and redox or ionization potentials [ 35 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that for lumiflavin in solution, using a few quantum mechanically treated water molecules nearby as well as a hybrid ONIOM/PCM approach to treat long-range electrostatic effects of the solvent is necessary to simulate the experimental FTIR spectrum. We note also the importance of long-range interactions for simulating other properties in the condensed phase, such as UV–visible spectra and redox or ionization potentials [ 35 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%